IMPROVING THE STUDENTS’ABILITY IN SPEAKING BY USING ROLE PLAYING METHOD IN THE DRAMA LESSON OF ENGLISH DEPARTMENT AT 2015/2016 ACADEMIC YEARS - Diani Syahputri Syahputri (State Islamic University of North Sumatra Indonesia, 2017)
Abstract. The aim of this study was to describe the improvement of the students’ achievement in speaking by Role Playing at Drama lesson at English department at Faculty of Teacher Training and Education University of Muhammadiyah of North Sumatra. The specific aim was how using to apply role play in studying drama and how the role play method can improve the students’ achievement in speaking. This research was used an action research that used two cycles. The subject of the study was 42 students at Academic 2015 – 2016 from English Department. The instrument of research was speaking test, questioners and observation to collect the data. Technique for collecting data was descriptive qualitative and quantitative. Technique for analyzing data was used descriptive which describe the finding of research which used some tables, frequency which was benefit to describe the achievements of the students in speaking from pre-test, and cycle 1 up to cycle 2. The finding of research was the students’ achievement in speaking were good by using Role playing which conducted one semester. Based on the data, the students’ achievements got improvement in every cycle. The students got A was 23.8 %, B/A and B 76,1 % and there were not students got C/B and D and E. It meant the indicators of this research could achieve by using Role playing at drama lesson when we compared with conventional method. The study by using role playing is more interested than conventional method. Key words: Improvement, Speaking Achievement, Role Play